Study of Solublity Behaviour of Some New Varieties of Oil Seeds - Ingale, Satish; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
The protein solubilization at different pH ranging from 0.5 to 13.5 were studied on some new varieties of oil seeds, viz., sunflower (Helianths annus) LSF-11, sunflower (Helianths annus) LSF-8, safflower (Carthamus tinctorius) PBNS-12, safflower (Carthamus tinctorius) PBNS-40 and groundnut (Arachis hypogea) JL-24.